Methodologies for applying calcium compounds in agropastoral systems: Changes in soil chemical attributes - Borges, Wander L. B.; Hipólito, Jorge L.; de Souza, Isabela M. D. [UNESP]; Juliano, Pedro H. G. [UNESP]; Rodrigues, Letícia N. F. [UNESP]; Andreotti, Marcelo [UNESP] (Wiley, 2022)
Soil pH values below 4.4 (acidity) limit nutrient availability and root exploration, whereas a pH range of 5.4–6.4 ensures the availability of most nutrients essential for crops. To ameliorate acidity in the surface and subsurface layers and improve soil chemical fertility, different application methodologies (surface, incorporation by soil tillage, or subsurface) for calcium (Ca) compounds (limestone [LS], phosphogypsum [PG], and hydrated lime [HL]) were evaluated in an Arenic Hapludult in an agropastoral system in Brazil. The experimental design comprised randomized blocks with four replications of seven treatments. After three seasons, all methodologies corrected surface acidity (0.0–0.2 m) by increasing pH and base saturation (BS) and reducing total acidity, but only subsurface application of HL plus surface application of PG in the first year and surface application of HL in subsequent years increased pH and BS in the subsurface (0.4–0.8 m). Consequently, incorporation of LS and subsurface application of HL in the first year are necessary to reduce total acidity in the subsurface (0.4–0.8 m) in subsequent years. Applying LS or HL plus PG increased sulfur (S)–SO4 content throughout the soil profile (0.0–0.8 m). In addition, in the 0.0-to-0.2-m layer, applying LS plus PG increased Ca2+ content and Ca2+/cation exchange capacity (CEC), and applying HL plus PG increased magnesium (Mg)2+ content and Mg2+/CEC. However, these results may be specific to the agronomic conditions of the trial; future studies should evaluate whether the timing of changes in soil chemical fertility varies depending on soil type.